COMPARATIVE ASSESSMENT OF THE NUTRITIONAL STATUS FOR BARU (Dipterix alata) SEEDLINGS - Boni, Thais Soto [UNESP]; Maltoni, Katia Luciene [UNESP]; Buzetti, Salatier [UNESP]; Rodrigues Cassiolato, Ana Maria [UNESP] (Centro Pesquisas Florestais, Ufsm, 2016)
To a successful revegetation process, besides improving the edaphic area conditions, seedlings must have good quality, which can be assessed by nutritional status. This research evaluated the foliar contents of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn, and Zn from Dipteryx alata seedlings produced under full sun or protected condition (30% of shade), using degraded soil as substrate, with or without organic residue added (32 t ha(-1) macrophyte) and with different phosphorus doses (0, 100, 200 e 300 mg dm(-3) P2O5), comparatively to seedlings and adult plants collected in the field. To each leaf sampling in the field, the soil was collected and analyzed for P, MO, pH, K, Ca, Mg, H+Al, SB and CTC. The same analysis was performed in the experimental units at the end of the experiment. The data showed that the Dipteryx alata presents low P requirement. The foliar levels, in seedling from field were higher than in adult plants, for N, P, K, and S, and lower for Ca, and the plant's developing stadium did not affect the foliar levels of Mg, B, Cu, Fe, Mn and Zn. The organic residue was not enough to supplies the needed N to seedlings produced under experimental conditions. The cultivation under full sun provided higher foliar concentrations of N, P, Ca, Mg, B, Cu, Fe and Mn. The foliar levels of N, P, K, Ca, B, Fe and Zn were higher in the presence of organic residue.
Keywords: degraded soil; organic residue; savannah